The Queen of Sheba in the Mystical Thought of Ibn ‘Arabī - Ismail Lala (Religions, 2023)
The mystical commentary on the story of Bilqīs, the Queen of Sheba, from chapter 27 of the Qur’an carried out by the highly influential Sufi thinker Muḥyī al-Dīn ibn ‘Arabī (d. 638/1240), shows that he differs radically from exoteric Sunni exegetes. The principal reason for this is Ibn ‘Arabī’s complete reliance on spiritual unveiling (kashf) as a hermeneutic tool. In the chapter on Sulaymān of Fuṣūṣ al-ḥikam, Ibn ‘Arabī represents Bilqīs as the most perspicuous instantiation of the divine Name, “the Compassionate” (Al-Raḥmān). It is the divine trait of compassion, says Ibn ‘Arabī, that provides the existentiating impetus required to bring forth the entire cosmos. Due to her personification of this trait, Bilqīs’ ascent to the pinnacle of gnosis and her ontological superiority over her peers is extolled by Ibn ‘Arabī in her Qur’anic story.